Tobacco smoke augments Porphyromonas gingivalis-Streptococcus gordonii biofilm formation. - Juhi Bagaitkar; Carlo A Daep; Carol K Patel; Diane E Renaud; Donald R Demuth; David A Scott (PLoS ONE)
Smoking is responsible for the majority of periodontitis cases in the US and smokers are more susceptible than non-smokers to infection by the periodontal pathogen Porphyromonas gingivalis. P. gingivalis colonization of the oral cavity is dependent upon its interaction with other plaque bacteria, including Streptococcus gordonii. Microarray analysis suggested that exposure of P. gingivalis to cigarette smoke extract (CSE) increased the expression of the major fimbrial antigen (FimA), but not the minor fimbrial antigen (Mfa1). Therefore, we hypothesized that CSE promotes P. gingivalis-S. gordonii biofilm formation in a FimA-dependent manner. FimA total protein and cell surface expression were increased upon exposure to CSE whereas Mfa1 was unaffected. CSE exposure did not induce P. gingivalis auto-aggregation but did promote dual species biofilm formation, monitored by microcolony numbers and depth (both, p<0.05). Interestingly, P. gingivalis biofilms grown in the presence of CSE exhibited a lower pro-inflammatory capacity (TNF-α, IL-6) than control biofilms (both, p<0.01). CSE-exposed P. gingivalis bound more strongly to immobilized rGAPDH, the cognate FimA ligand on S. gordonii, than control biofilms (p<0.001) and did so in a dose-dependent manner. Nevertheless, a peptide representing the Mfa1 binding site on S. gordonii, SspB, completely inhibited dual species biofilm formation. Thus, CSE likely augments P. gingivalis biofilm formation by increasing FimA avidity which, in turn, supports initial interspecies interactions and promotes subsequent high affinity Mfa1-SspB interactions driving biofilm growth. CSE induction of P. gingivalis biofilms of limited pro-inflammatory potential may explain the increased persistence of this pathogen in smokers. These findings may also be relevant to other biofilm-induced infectious diseases and conditions.